Analisis Usability dan User Experience Sistem Informasi Primary Care BPJS Kesehatan di Puskesmas Karanganyar Menggunakan Metode System Usability Scale (SUS) dan User Experience Questionnaire (UEQ) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the usability and user experience of the Primary Care (P-Care) BPJS Kesehatan Information System at Puskesmas Karanganyar, Gandusari District, Trenggalek Regency. P-Care is a mandatory web-based application used by all primary healthcare facilities (FKTP) to manage services for National Health Insurance (JKN) participants. A quantitative descriptive approach was employed using two standardized instruments: the System Usability Scale (SUS) for usability measurement and the User Experience Questionnaire (UEQ) for assessing user experience across six dimensions—Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. Total sampling involved all 33 active users comprising administrative staff, nurses, midwives, and medical personnel. SUS analysis yielded a mean score of 64.39 (OK/Acceptable category). UEQ results showed all six dimensions in the Good category: Attractiveness (1.37), Perspicuity (1.37), Novelty (1.34), Dependability (1.33), Efficiency (1.29), and Stimulation (1.27), with none reaching the Excellent threshold (≥1.5). Recommendations include navigation simplification, server optimization, auto-save features, extended session duration, and interface redesign.